ANALISIS BIPLOT UNTUK RETURN ON ASSET (ROA) DAN RETURN ON EQUITY (ROE) PADA PERUSAHAAN ASURANSI JIWA NASIONAL - Novika, Fanny; Saptyarani, Amelia (P3M Trisakti School of Insurance (TSI), 2021)
Biplot analysis is a type of multivariate analysis used to solve problems or process data that involves many variables. The number of variables in a data often makes it difficult to represent the results. Therefore, Biplot is a media solution for describing the data in the summary table in a two dimensional graph. This analysis can be applied to find out information about the relative position, similarity of characteristics between objects and the diversity of variables or variables in the elements of return on assets and return on equity in national life insurance companies related to aspects of a health assessment and company grouping. The results of the biplot analysis show two categories, namely grouping based on biplot points and year variability. There are differences in the results of national life insurance groupings, namely the AJB Bumiputera 1912 company, Central Asia Raya Life Insurance, Equity Life Indonesia, Heksa Solution Insurance, Jiwasraya Insurance, Indosurya Sukses Life Insurance. Meanwhile, national life insurance companies that have the same characteristics for return on assets and return on equity are divided into 3 (three) groups. In the management aspect, namely related to life insurance companies that are stable and healthy in investing, ROA and ROE are shown by group III. The greatest and most dominant diversity of years for return on assets lies in 2018, while for return on equity, the greatest diversity is in 2019. There is a difference in the results of the variation in ROA and ROE due to the variable used differently. ROA shows aspects of assets consisting of liabilities and equity. If the acquisition of large assets, it can be used to pay corporate liabilities. ROE only shows from the side of equity without paying attention to liabilities.